Pre-operative nutritional status affects enteral feeding in post-operative period among pediatric laparotomy cases - Singh, Santosh Kumar; Agrawal, Nitika; Das, Kunal; Naaz, Aisha (International Journal of Contemporary Pediatrics, 2018)
Background: Early introduction of enteral feed in postoperative settings, although advocated, is not practiced universally. This study reviews post-operative feeding practices amongst pediatric surgery cases and variables affecting it. Methods: A retrospective analysis was done for children operated for abdominal conditions during 2013-2015. Data were analyzed for pre-operative variables, operative indications and procedure, post-operative events and feeding practices. Results: Seventy children underwent laparotomy during study period. Median time of starting enteral nutrition was 3rd post-operative day and full feed attainment was day 6. Severely thin/malnourished children could be started on enteral feed on 3.89+1.76 days while normal nourished children were started on 2.2+0.87 days (p<0.05). Eleven cases noted interruption of feed, regurgitation was the commonest cause. Cases of abdominal Koch’s and cases requiring gut incision showed delay in feed onset. Conclusions: Post-operative onset of enteral feed and tolerance depends on pre-surgery nourishment status, baseline disease condition and type of surgery.